The Effect of Ginger Brew on the Intensity of Dysmenorrhea Pain at Touluaan Vocational School, North Minahasa - Patricia Anggelina Arikalang; Reny Retnaningsih (Detector: Jurnal Inovasi Riset Ilmu Kesehatan, 2025)
Dysmenorrhea is one of the most common gynecological complaints experienced by adolescent girls and can impact academic performance and quality of life. Pharmacological therapy is commonly used for dysmenorrhea management, but its use in adolescents is often limited by side effects and a tendency to self-medicate. Therefore, non-pharmacological alternatives are needed that are safe, easy to implement, and appropriate for the adolescent context. One complementary therapy that has the potential to reduce dysmenorrhea pain is ginger (Zingiber officinale), which has anti-inflammatory and analgesic effects. This study aimed to analyze the effect of ginger infusion on dysmenorrhea pain intensity in female students at Touluaan Vocational High School in North Minahasa. The study used a quasi-experimental design with a one-group pretest–posttest approach. The study sample consisted of 32 female students experiencing dysmenorrhea, selected using a purposive sampling technique. Pain intensity was measured using a Numeric Rating Scale (NRS) before and after administration of the ginger infusion. The intervention consisted of consuming the ginger infusion twice daily for the first two days of menstruation. Data were analyzed using univariate analysis and the Wilcoxon Signed Rank Test with a significance level of p < 0.05. The results showed a decrease in dysmenorrhea pain intensity after administering ginger infusion. Statistical analysis showed a significant difference between pain intensity before and after the intervention (p < 0.05). The conclusion of this study indicates that ginger infusion has a significant effect on reducing dysmenorrhea pain intensity and can be recommended as a safe and applicable non-pharmacological complementary therapy for adolescent girls in school environments.